Hinged and Wide: A New P^P Ligand for Emissive [Cu(P^P)(N^N)][PF(6)] Complexes - Keller, Sarah (Molecules, 2019)
Heteroleptic [Cu(BIPHEP)(N^N)][PF(6)] complexes (BIPHEP = 1,1′-biphenyl-2,2′-diylbis(diphenylphosphane)), in which N^N is 2,2′-bipyridine (bpy), 6-methyl-2,2′-bipyridine (6-Mebpy), 6-ethyl-2,2′-bipyridine (6-Etbpy), or 5,5′-dimethyl-2,2′-bipyridine (5,5′-Me(2)bpy), have been synthesized and characterized using multinuclear NMR spectroscopies and electrospray ionization mass spectrometry. The single crystal structures of [Cu(BIPHEP)(bpy)][PF(6)]∙CH(2)Cl(2), [Cu(BIPHEP)(5,5′-Me(2)bpy)][PF(6)]∙CH(2)Cl(2), [Cu(BIPHEP)(6-Mebpy)][PF(6)]∙Et(2)O∙0.5H(2)O and [Cu(BIPHEP)(6-Etbpy)][PF(6)] confirm distorted tetrahedral {Cu(P^P)(N^N)} coordination environments. Each compound shows a quasi-reversible Cu(+)/Cu(2+) process. In deaerated solution, the compounds are weak emitters. Powdered samples are yellow emitters (λ(em)(max) in the range 558–583 nm) and [Cu(BIPHEP)(5,5′-Me(2)bpy)][PF(6)] exhibits the highest photoluminescence quantum yield (PLQY = 14%). On cooling to 77 K (frozen 2-methyloxolane), the emission maxima are red-shifted and the excited state lifetimes increase from τ(1/2) < 8 μs, to τ(1/2) values of up to 53 μs, consistent with the compounds with N^N = 6-Mebpy, 6-Etbpy and 5,5′-Me(2)bpy exhibiting thermally activated delayed fluorescence (TADF).